2018
DOI: 10.24815/jts.v7i2.12351
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Vs30 Lokasi Kecamatan Syiah Kuala Dalam Upaya Mitigasi Bencana Gempa Bumi Kota Banda Aceh

Abstract: Banda Aceh is located at the geological segment vulnerable to earthquake. However as the capital of the Aceh province should be a serious concern in order to minimize the impact of the devastating earthquake. Therefore, the assessment of soil layer amplification using shear wave velocity values is done as one of the disaster mitigation efforts. Shallow seismic testing to get the parameters of shear wave by using MASW method. The results showed that Syiah Kuala subdistrict is divided into two zones of soil laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The site coefficient for Banda Aceh city was determined using shear-wave velocity travel-time averaged over a depth of 30-m (Vs30) data from Muzli et al (2014) and Jamaluddin et al (2018) in order to calculate the amplification factor. Muzli et al (2014) and Jamaluddin et al (2018) determined Vs30 using the MASW (Multichannel Analysis of Surface Wave) method from 53 locations, which were placed approximately 1 km apart. The result showed that the Banda Aceh area has stiff and soft soil layers.…”
Section: Site Coefficient and Liquefaction Effectmentioning
confidence: 99%
See 3 more Smart Citations
“…The site coefficient for Banda Aceh city was determined using shear-wave velocity travel-time averaged over a depth of 30-m (Vs30) data from Muzli et al (2014) and Jamaluddin et al (2018) in order to calculate the amplification factor. Muzli et al (2014) and Jamaluddin et al (2018) determined Vs30 using the MASW (Multichannel Analysis of Surface Wave) method from 53 locations, which were placed approximately 1 km apart. The result showed that the Banda Aceh area has stiff and soft soil layers.…”
Section: Site Coefficient and Liquefaction Effectmentioning
confidence: 99%
“…3 was taken from the global Vs30 model developed by Allen and Wald (2009), yet for small scale (see Fig. 7a), the Vs30 data were derived from Muzli et al (2014) and Jamaluddin et al (2018). These data then were applied in GIS analysis to produce the earthquake scenario ground motions shown in Fig.…”
Section: Earthquake Intensity Modelsmentioning
confidence: 99%
See 2 more Smart Citations